DEVICE FOR REMOVAL OF INADVERTENTLY LEFT DRAINAGE TUBE IN THE FIELD OF SURGERY - Mamedov, A. A.; Turkov, P. S. (Travmatologii͡a︡ i ortopedii͡a︡ Rossii, 2013)
The paper presents a description of the device for removal of surgical drains, developed at Novosibirsk RITO, and the experience of its application at the Department of Joint Replacement and Endoscopic Surgery. The device enables to remove a drainage tube or its fragments from a surgical site completely and with minimal damage to surrounding soft tissues in case of its breakage or a threat of breakage. This prevents revision surgery to remove the drain or its fragment, and eliminates the possibility of secondary infection of the wound and complication development.